Application of Manure Rather Than Plant-Origin Organic Fertilizers Alters the Fungal Community in Continuous Cropping Tobacco Soil - Su, Yan; Zi, Haiyun; Wei, Xiaomeng; Hu, Binbin; Deng, Xiaopeng; Chen, Yi; Jiang, Yonglei (Frontiers in Microbiology, 2022)
Continuous cropping leads to serious fungal diseases and depleted yield of tobacco (Nicotiana tabacum), which would be mitigate by organic fertilization. Yet we know little about how organic fertilizers affect the fungal community of continuous cropping tobacco soil. In this study, we investigated the soil fungal community after 11 years tobacco planting with chemical fertilization (CF) or chemical fertilization combining organic fertilizers from plant or animal origins, including oil cake (CFO), straw (CFS) and farmyard fertilizer (CFM). The predominant phyla of Ascomycota (70%) and Mortierellomycota (15%) were identified in all treatments. A significantly higher proportion of Pyrenochaetopsis but lower relative abundance of Sordariomycetes were observed in the CFM compared with the controls. Compared to CF and the non-fertilized control (CK), CFO and CFS led to higher species richness (P <0.05), while CFM led to less uniform fungal community, indicating by lower Shannon and higher Simpson diversity index (P < 0.05). Pearson correlation and Redundancy analysis suggested that fertilizations primarily influenced the fungal community via altering the soil nutrient conditions, among which soil organic carbon and total phosphorus significantly correlated with the fungal diversity and community composition (P < 0.05). Notably, FUNGuild annotation suggested that while other treatments showed no significant effect on the fungal trophic modes, CFM strongly increased the Saprotroph fungi by more than 30% (P < 0.05), thus prevented the prevalent of potential pathotypes and symbionts. The results suggest that the type of organic fertilizers is essential to the effect of long-term organic application on fungal community, and the animal-origin manure seems a better chose than plant-origin materials in in continuous cropping tobacco field.